Lipid metabolism in Th17 cell function - Kanno, Toshio; Nakajima, Takahiro; Miyako, Keisuke; Endo, Yusuke (Pharmacology & therapeutics (Oxford), 2023)
Among the subset of T helper cells, Th17 cells are known to play a crucial role in the pathogenesis of various autoimmune disorders, such as psoriasis, rheumatoid arthritis, inflammatory bowel disease, steroid-resistant asthma, and multiple sclerosis. The master transcription factor retinoid-related orphan receptor gamma t (RORγt), a nuclear hormone receptor, plays a vital role in inducing Th17-cell differentiation. Recent findings suggest that metabolic control is critical for Th17-cell differentiation, particularly through the engagement of de novo lipid biosynthesis. Inhibition of lipid biosynthesis, either through the use of pharmacological inhibitors or by the deficiency of related enzymes in CD4+ T cells, results in significant suppression of Th17-cell differentiation. Mechanistic studies indicate that metabolic fluxes through both the fatty acid and cholesterol biosynthetic pathways are essential for controlling RORγt activity through the generation of a lipid ligand of RORγt. This review highlights recent findings that underscore the significant role of lipid metabolism in the differentiation and function of Th17 cells, as well as elucidating the distinctive molecular pathways that drive the activation of RORγt by cellular lipid metabolism. We further elaborate on a pioneering therapeutic approach for ameliorating autoimmune disorders via the inhibition of RORγt.